Effectiveness of Proton Pump Inhibitors as a Gastrointestinal Bleeding Prophylaxis in Intensive Care Unit: Systematic Review and Meta-Analysis - Fonny Cokro; Jenny Jokimawidjaja (Journal of Urban Health Research, 2022)
Introduction: GI bleeding is a serious illness that can lengthen the time spent in the Intensive Care Unit (ICU) and increase morbidity and death by up to four times. Proton Pump Inhibitors (PPIs) are agents commonly used in patients to prevent Gastrointestinal (GI) bleeding in ICU. However, nowadays, the use of PPIs to prevent GI bleeding is being concerned due to the emergence of various studies regarding the side effects caused by PPIs. We conducted a systematic review and meta-analysis to see the magnitude of the effectiveness and validate the safety of PPIs. Methods: We searched through PubMed, ScienceDirect, GARUDA Portal, Clinical Key, and Google Scholar databases to identify randomized controlled trials (RCTs) that compared the effects of PPI administration on the PPI and placebo groups in adults ICU patients. Results: From a total of 8 studies, this meta-analysis shows the effectiveness of PPIs as prophylactic GI bleeding significantly with p < 0.0001, RR = 0.52 (95% CI 0.38-0.71). Regarding safety, PPIs did not significantly increase the risk of pneumonia (p = 0.30, RR = 1.31 (95% CI 0.78-2.20)); and C. difficile infection (p = 0.90, RR = 0.91 (95% CI 0.21-3.85); and it does not impact on the mortality event (p = 0.78; RR 1.01 (95% CI 0.93-1.10). Conclusions: PPIs reduce GI bleeding in ICU patients over the age of 18. PPIs are also safe to use as preventative GI bleeding with no increased risk of pneumonia and C. difficile infection. PPI does not, however, significantly affect the death rates.